2009
DOI: 10.1016/j.nuclphysbps.2009.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Preheating after Multi-Field Inflation

Abstract: In this note I study preheating after multi-field inflation to assess the feasibility of parametric resonance.An intuitive argument for the suppression of resonances due to dephasing of fields in generic multi-field models is presented. This effect is absent in effective single field models, rendering them inappropriate for the study of preheating. * Electronic address: diana.battefeld(AT)helsinki.fi

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The interval for g is not particularly wide, but allowed values do not appear to be overly fine tuned either and cover the same range commonly considered for studies of preheating after inflation [104,123,124]. In fact, the fields at ESPs in the vicinity of the final resting place can act as preheat matter fields, as investigated in [106]: there, it was found that preheating is qualitatively different than in models that have an ESP at the VEV of the inflatons; while de-phasing of inflatons tends to suppress parametric resonance [116][117][118][119] (see [118,125,126] for the case of two inflations, that still permits resonances), two new effects leading to efficient preheating were found: particle production during the first in-fall can already comprise a seizable energy transfer if the trapped inflation regime lasts until preheating commences, but it is never complete. Subsequent broad resonance is generically suppressed due to de-phasing of the fields, but if an 8 Taking e.g.…”
Section: The Power-spectrum From Back-scatteringmentioning
confidence: 98%
See 1 more Smart Citation
“…The interval for g is not particularly wide, but allowed values do not appear to be overly fine tuned either and cover the same range commonly considered for studies of preheating after inflation [104,123,124]. In fact, the fields at ESPs in the vicinity of the final resting place can act as preheat matter fields, as investigated in [106]: there, it was found that preheating is qualitatively different than in models that have an ESP at the VEV of the inflatons; while de-phasing of inflatons tends to suppress parametric resonance [116][117][118][119] (see [118,125,126] for the case of two inflations, that still permits resonances), two new effects leading to efficient preheating were found: particle production during the first in-fall can already comprise a seizable energy transfer if the trapped inflation regime lasts until preheating commences, but it is never complete. Subsequent broad resonance is generically suppressed due to de-phasing of the fields, but if an 8 Taking e.g.…”
Section: The Power-spectrum From Back-scatteringmentioning
confidence: 98%
“…As long as the potential is steep enough, the trajectory is traversed at this constant speed; thus, functional fine tuning, i.e., the η problem, is relaxed. Preheating was discussed in [106], entailing qualitatively new resonance effects: efficient preheating is likely for dense distributions, x 0.001, in contrast to preheating with a single ESP at the VEV of the inflatons [116][117][118][119].…”
Section: Introductionmentioning
confidence: 99%
“…We wish to include several preheat "matter" fields that become light at different ESPs in the vicinity of | ϕ| = 0; we deliberately avoid putting an ESP at | ϕ| = 0, since preheating of such a field is well understood (see [8,9,15,38,[40][41][42]84] for a small, non-representative collection, with particular focus on multiple inflatons) and generally suppressed if N > few [15,[38][39][40].…”
Section: Matter Fieldsmentioning
confidence: 99%
“…An observable by-product of preheating can be gravitational waves [28][29][30][31][32][33][34][35][36][37]. The majority of these phenomenological studies focus on one (see the reviews [1,2]) or several [15,[38][39][40][41][42] inflaton fields, coupled to a single degree of freedom that becomes light at the vacuum expectation value (VEV) of the inflatons. For example, in standard, single-field chaotic inflation with potential V (ϕ) = m 2 ϕ 2 /2, one can introduce another light scalar field that couples to the inflaton via the interaction Lagrangian L = −g 2 χ 2 ϕ 2 /2, such that the effective mass of χ is minimal at the VEV ϕ = 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation